MODERN VIEW ON THE FEATURES OF PATHOMORPHOLOGICAL CHANGES IN THE PLACENTA IN THE 3rd-8TH WEEKS OF PREGNANCY (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The article draws attention to the significant advances in genetics and biology, which have made it possible to expand our understanding of the molecular basis and mechanisms of histo- and organogenesis. She emphasizes that the structural basis of interactions between mother and fetus is formed as a result of complex processes of cellular differentiation that determine the development of the fetus and its organs. The article points to the significant role of chronic placental insufficiency in the structure of perinatal morbidity and mortality. This article summarizes current research in the field of placental insufficiency and fetal growth restriction syndrome, highlighting its importance and implications in perinatal medicine.